Poslušanje pri pouku književnosti - Vogel, Jerica (Jezik in slovstvo, 1999)
Listening in a basic, frequent and important communicative activity. This makes the ability to listen one of the fundamental components of the total communicative capacity. It is nowadays recognised that the listening ability is not automatic, that it has to be learnt the same way as e.g. the ability to read or write. Accepting this fact, the current reform of the Slovene language and literature curricula has introduced practicing Slovene language and literature and non-literary and non-literary texts. The paper deals with theoretical and practical aspects of teaching listening in literature classes.
Keywords: književnost; literature; pouk; poslušanje